The diachrony of Welsh subject pronouns - Meelen, Marieke; Willis, David (Studia Celtica Posnaniensia, 2024)
In many languages, independent pronouns become reduced to inflectional affixes which are ultimately lost, resulting in the creation of new independent pronouns. The loss of null subjects therefore often goes hand in hand with a loss of agreement morphology on the verb. Inflectional morphology has remained virtually unchanged from the Middle Welsh period up to the present day, but whereas null subjects were frequently found in the earliest period, in Present-day spoken Welsh overt pronouns are generally preferred. In this article we present a pilot study of the history of subject pronouns in Welsh based on six annotated texts from the Parsed Historical Corpus of the Welsh Language (PARSHCWL) from three different time periods (fourteenth, sixteenth and eighteenth centuries), as well as in translated and non-translated texts. We show that null subjects are favoured in all periods and use a mixed-effects logistic regression model to test which factors have an effect on whether the subject pronoun is overt or null and if this distribution changes over time.